No Growth without Equity? Inequality, Interests, and Competition in Mexico - Levy, Santiago; Walton, Michael (Washington, DC: World Bank and Palgrave Macmillan, 2013)
In this introduction, the authors do three things. They first introduce the puzzle and relate it to existing interpretations from market reformists and their critics, arguing that both sets of views are inadequate. The authors then offer an alternative interpretation: that entrenched inequities sustained by a rent-sharing political equilibrium are a primary source of inefficiencies and weak growth. Moreover, this equilibrium has been resilient to democratization in ways that can be explained by the nature of the underlying forces. Finally, they draw some tentative implications for the future, suggesting how public action could potentially support a shift to more equitable and more efficient equilibrium. The volume's chapters are introduced within the structure of this argument.